2014
DOI: 10.5603/ep.2014.0045
|View full text |Cite
|
Sign up to set email alerts
|

Akromegalia — nowe spojrzenie na pacjenta. Polskie propozycje postępowania diagnostyczno-terapeutycznego w akromegalii w świetle aktualnych doniesień

Abstract: Acromegaly is a rare disease caused by the secretion of growth hormone (GH) in excess, in most cases from a pituitary tumour. The diagnosis is usually delayed and is often associated with the development of various complications causing premature mortality. In patients with hypertension, heart failure, diabetes, and arthropathy that is non-specific for age, attention should be paid to the occurrence of somatic signs of acromegaly. As a screening test, insulin-like growth factor-1 (IGF-1) concentration should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 27 publications
2
29
0
3
Order By: Relevance
“…Surgery is the first-line treatment of acromegaly and often is followed by pharmacological therapy and radiotherapy [3]. Transsphenoidal resection of a pituitary tumour either removes or substantially decreases the size of the tumour, thus preventing intracranial complications [1].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is the first-line treatment of acromegaly and often is followed by pharmacological therapy and radiotherapy [3]. Transsphenoidal resection of a pituitary tumour either removes or substantially decreases the size of the tumour, thus preventing intracranial complications [1].…”
Section: Introductionmentioning
confidence: 99%
“…therefore, the most serious complications of acromegaly, especially with concomitant diabetes, are cancers, mainly of the gastrointestinal tract, but also of other organs: breast, prostate, brain [2,9,10,13,16]. in the group of 106 patients suffering from acromegaly with concomitant diabetes, wen-ko et al demonstrated a higher prevalence of cancers as compared to patients with acromegaly without diabetes (13.2% vs. 3.5%; p < 0.01) [12].…”
Section: Discussionmentioning
confidence: 99%
“…the consequence of the disease is the excessive production of growth factors (mainly insulin-like growth factor-1, igF-1), which leads to characteristic changes in the appearance of patients, organ and metabolic complications and neoplasms [1,2]. slow changes in appearance and the rich symptomatology of acromegaly are a frequent cause of diagnostic errors in the practice of general Practitioners and delay diagnosis of the disease by an average of 5-10 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypersecretion of GH and IGF1 effect the whole body and lead to multisystemic complications, including those involving the gastrointestinal system [2,3]. In terms of organic gastrointestinal disorders, adenomatous polyps and colon carcinoma are the most significant complications associated with acromegaly [4].…”
Section: Introductionmentioning
confidence: 99%